Fasciocutaneous Free Flaps Are More Reliable Than Muscle Free Flaps in Lower Limb Trauma Reconstruction: Experience in a Single Trauma Center - Sofiadellis, Foti; Liu, David S.; Webb, Angela; MacGill, Kirsty; Rozen, Warren Matthew; Ashton, Mark W. (Journal of Reconstructive Microsurgery, 2012)
Background Muscle (M) and fasciocutaneous (FC) free flaps are frequently used options in the reconstruction of traumatic lower limb injuries. The use of one flap over another has remained the topic of controversy in the literature. With a large experience, we sought to evaluate key outcomes of M versus FC free flap reconstructions in lower limb trauma in a single trauma center.Methods A consecutive 7- year review of all free flap reconstructions for lower limb trauma performed at the Royal Melbourne Hospital was conducted. Patient data were prospectively entered into a unit database and retrospectively reviewed.Results One hundred three patients underwent 105 free flap reconstructions (M = 48 and FC = 57) in lower limb trauma. We experienced a rate of 2.9% total flap failures and 11.4% partial flap losses. Total flap failures represented 6.3% M and 0% FC flaps. The partial flap failures included 15.8% of M and 5.3% of FC flaps. Latissimus dorsi (40% of M group) and radial forearm free flaps (67% of FC group) were most commonly used in each group. There was a statistically significant difference between groups in rates of reoperation (M = 44% versus FC = 16%), postoperative infection (M = 38% versus FC = 12%), fracture nonunion (M = 40% versus FC = 21%), and donor site morbidity (M = 25% versus FC = 4%). Nonstatistically significant differences were encountered with higher rates of osteomyelitis (M = 14.6% versus FC = 10.5%), unplanned bone graft (M = 14.6 versus FC = 10.5%), and inability to bear full weight at 1 year (M = 30.2% versus FC = 17.0%) found in the M group. In our cohort, M flaps used for metal coverage resulted in higher rates of reoperation, postoperative infections, and flap loss than FC flaps (M = 61% versus FC = 25%, p < 0.05).Conclusion Statistically higher complication rates in key reliability markers were found in the M free flap group. This study found FC free flaps to be more reliable for reconstruction of lower limb injuries in a major trauma center.
Keywords: muscle flaps; fasciocutaneous; lower limb trauma; soft tissue defect; free flaps